2008
DOI: 10.1093/jnci/djn268
|View full text |Cite
|
Sign up to set email alerts
|

Familial Aggregation of Common Sequence Variants on 15q24-25.1 in Lung Cancer

Abstract: Three recent genome-wide association studies identified associations between markers in the chromosomal region 15q24-25.1 and the risk of lung cancer. We conducted a genome-wide association analysis to investigate associations between single-nucleotide polymorphisms (SNPs) and the risk of lung cancer, in which we used blood DNA from 194 case patients with familial lung cancer and 219 cancer-free control subjects. We identified associations between common sequence variants at 15q24-25.1 (that spanned LOC123688 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
96
1
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(99 citation statements)
references
References 20 publications
1
96
1
1
Order By: Relevance
“…A systematic and comprehensive description of all the observations is beyond the scope of this review, which focuses on the role of nAChRs in ND. It is noted that the association of the rs8034191 and rs1051730 SNPs with familial LC was described by Liu et al 102 in the context of GWAS performed on a 194 familial LC patients and 219 control individuals sample (adjusted for age, sex and pack-years of cigarette exposure). However, data regarding ND in terms of FTND scores were unavailable.…”
Section: Chrna5-chrna3-chrnb4 and Lcmentioning
confidence: 89%
See 1 more Smart Citation
“…A systematic and comprehensive description of all the observations is beyond the scope of this review, which focuses on the role of nAChRs in ND. It is noted that the association of the rs8034191 and rs1051730 SNPs with familial LC was described by Liu et al 102 in the context of GWAS performed on a 194 familial LC patients and 219 control individuals sample (adjusted for age, sex and pack-years of cigarette exposure). However, data regarding ND in terms of FTND scores were unavailable.…”
Section: Chrna5-chrna3-chrnb4 and Lcmentioning
confidence: 89%
“…However, data regarding ND in terms of FTND scores were unavailable. 102 In a very recent follow-up publication to the GWAS of Amos et al 101 Spitz et al 103 combined the discovery and one of the replication samples and observed that the highly correlated rs1051370 and rs8034191 are significant risk factors for both LC and ND, contrary to the initial conclusions of Amos et al 103 (Supplementary Table 1). Two ND-related phenotypes were found to be significantly associated: CPD and FTND, but not other phenotypes such as age of SI.…”
Section: Chrna5-chrna3-chrnb4 and Lcmentioning
confidence: 97%
“…The replicated nicotine dependence loci tagged by rs16969968 (96,(100)(101)(102) and rs578776 (101,103) have also been reported to influence lung cancer risk in several genomewide association studies. This is an exciting convergence of findings for nicotine dependence risk loci and lung cancer risk loci.…”
Section: Origins Of Cellular and Subcellular Selectivitymentioning
confidence: 90%
“…Several GWAS have identified a region of 15q25.1, containing nicotinic acetylcholine receptor subunit genes CHRNA3 and CHRNA5, associated with lung cancer, nicotine addiction, cigarettes smoked per day, COPD, FEV 1 , and emphysema (59)(60)(61)(62)(63)(64)(65)(66)(67)(68). Additional regions of interest identified in lung cancer GWAS are on 3q29, 5p15, 6p21, 10q25, and 15q15 (69)(70)(71).…”
Section: Gwasmentioning
confidence: 99%